THE INFLUENCE OF FUNDAMENTAL FACTORS ON STOCK RETURN (Case Study: Company Listed in LQ45 2011-2014) - Tamunu, Sonnia Cindy; Rumokoy, Farlane (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Consumption and investment are the two things are related because, delay consumption at a time could be interpreted as an investment that is used for future consumption. The investment is an investment for one or more assets owned and usually in a long period of time with the hope of obtaining a profit in the future. Investments can be classified into direct investment and indirect investment. Direct investment made by purchasing directly from a company's financial assets either through intermediaries or by any other means. One of which is included in direct investment. Fundamental and technical information can be used as a basis for investors to predict the return, risk or uncertainty, the amount, timing, and other factors associated with investment activities in the capital market. Based on the problem background above the purpose of this research is to analyze the effect ROA, CR, EPS, and NPM influence on stock returns, partially and simultaneously. Using a regression method as a data analysis tools, this research found that ROA, CR, EPS, and NPM has significant influence on stock returns, partially and simultaneously. Â  Keywords: investment, fundamental, technical, investors, stock returns